الفهرس العام لمخطوطات المكتبة البارونية - الباروني, سعيد بن يوسف (2019)
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

Guide to collections relating to Oman (St Antony’s College, 2013)
Keywords: Inventaire – Oxford

Ancient Amazigh Poems Isefra Iqburen n Infusen - Buzakhar, Mazigh (2010)
Keywords: Poésie – Djebel Nefousa

Biography of Infusen (Nefusa) Issa Ahmed Said Mugsi Jadu (Fessatu area) - Buzakhar, Mazigh (TIRA for Research & Studies, 2014)
Keywords: Biographies – Djebel Nefousa – 20e siècle

Azel n Tẓilla wa u’nessin - Nouh-Mefnoune, Banouh (2014)
Keywords: Littérature – Mzab

Als Deutsch-Wituland gegen Helgoland getauscht wurde - Dornseif, Golf (2012)
Keywords: Zanzibar

Ouafakat : sur les affrontements meurtriers dans la vallé du M'zab. Décembre 2013 - janvier 2014 - G.S. (2014)
Keywords: Conflits – Mzab

I manoscritti berberi : un patrimonio inesplorato - Brugnatelli, Vermondo (2012)
Keywords: Linguistique

Middle East stability : Saudi muscles, Oman diplomacy - Assl, Nima Khorrami (Defence Viewpoints from UK Defence Forum, 2011)
Keywords: Politique étrangère – Oman – 1970-2020

Catalog of Ibadi Manuscripts at the Special Collections Library of the Università degli Studi di Napoli L’Orientale فهرس المخطوطات الإباضية في مكتبة الكتب النادرة في جامعة نابولي "الشرقية" - Love Jr, Paul M. (2017)
Keywords: Catalogue – Naples; Manuscrits – Naples

What was the influence of battle of Siffīn over Khārijites’ doctrine and why did they separate themselves from the Muslim community? - Yakar, Sumeyra (2014)

Preliminary Catalog of Arabic Manuscripts at the Association pour la Sauvegarde de l’Île de Djerba (Houmet Souk, Tunisia) - Love Jr, Paul M. (2018)
This a preliminary catalog of the Arabic manuscripts held at the Association pour la Sauvegarde de l’Île de Djerba (ASIDJ) on the island of Djerba, Tunisia. These manuscripts (bound volumes and assembled collections of fragments, representing many more titles) are all stored in acid-free boxes or folders. All items are housed in the association’s library in a former zawiya in the city of Houmet Souk. The association also has a sizeable collection of family and other documents in manuscript form that are awaiting cataloging—in case you are interested! Many of the manuscripts carry content related to the history of Ibadism (e.g. MS 013) and the history of Djerba (e.g. MS 01). For example, chronicles or legal compendia containing cases of disputes in Djerba, where there has been a sizeable Ibadi population for centuries.
Keywords: Bibliothèques – Djerba; Catalogue – Djerba; Manuscrits – Djerba

Ruling in the Name of the Revolution: The Local Grounding of Non-State Armed Groups in Western Libya - Merabti, Sara (University of Salento, 2019)
Since the fall of the Qadhafi regime, Libyan armed groups have emerged as the de facto power holders in many parts of the country. Much of the existing research on Libyan non-state armed groups has looked at the relation between the armed groups and the central authorities, or between the armed groups and other powerful actors. This article is based on fieldwork in four cities in Western Libya and shows that the armed groups should be understood as locally grounded actors. Several armed groups from local communities are seen as legitimate powerholders, because of their role during and after the revolution. Many of the armed groups also originate from the same ethnic and social group as the people they set out to rule, which creates a tacit social contract between the militias and the local population. I argue that the main factor which determines how the rule of armed groups in Libya plays out is the legacy of the Qhadafi regime and the revolution. This may have implications for the future organization of the Libyan state.

Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List - Bencini, Claudio (Fondazione Onlus, 2013)
Libyan Berber Heritage: Jefara, Adrar Nafusa and Hamada al Hamra Cultural Landscapes. A possible new Tentative Candidate for UNESCO List
Keywords: Archéologie – Djebel Nefousa